Analisis Potensi Penerimaan Retribusi Pelayanan Parkir di Tepi Jalan Umum Kota Banjarmasin - Rusyadi, Muhammad Reza; Imansyah, Muhammad Handry (PPJP ULM, 2019)
The purpose of this study was to see the true potential of revenue from the retributionof parking services on the edge of the public roads of Banjarmasin City in 2018. The type ofresearch used is descriptive statistics, with a population of 208 parking retribution points in5 sub-districts of Banjarmasin City and using the Slovin test to determine 22 samples. Thedata used are primary data obtained from field observations. The analysis technique used inselecting sampling and standard deviation techniques. Select sampling by observing for 10minutes parking reception at busy and quiet hours on weekdays and weekends. While thestandard deviation is used to see the upper and lower limits of potential retribution forparking service on the edge of public roads.The results obtained in this study show that the target set can cross the lowerstandard deviation, which means that the local government's performance, especially thetransportation agency, is quite good. Still, the revenue from the on-street parking retributioncan be improved. For the North Banjarmasin region, it can be increased by 101%. SouthBanjarmasin by 218%, then for the West Banjarmasin region by 26%, then for EastBanjarmasin by 26%, and the Central Banjarmasin area by 23%. Whereas for the centraantasari market, it can be increased by 29%